Analisis Efektivitas Sistem Pengendalian Manajemen Atas Penggajian Pegawai Dan Non Pegawai Pada Kantor Camat Medan Timur - Nurul Aqlina; Purwita Sari (Jurnal Mutiara Ilmu Akuntansi, 2023)
Effectiveness is a measurement in the sense of achieving predetermined goals. Management Control System is a collection of elements that are interconnected and interact in one unit to carry out a process of achieving a main goal. Salary is part of the largest compensation provided by the agency as remuneration for its workforce. The East Medan Sub-District Office located in the Medan area, North Sumatra is one of the government agencies that functions as a community service. The research that the author conducted aims to analyze the Effectiveness of the Management Control System for Employee and Non-Employee Payrolls at the East Medan Sub-District Office. This study uses qualitative research methods that are descriptive and tend to use analysis. The data collection stage is carried out through interviews, literature studies, and there is also an addition from searching on the website. The types of data used in this study are Primary and Secondary Data. In this study, the authors analyze the existing data using a Data Processing Application (Software NVivo 11 Plus), which can be proven by a Model (Brainware Analysis). Based on the analysis carried out, it was concluded that the cause of the delay in the effectiveness of the management control system on the payroll of employees and non-employees at the East Medan Sub-district Office, namely due to lack of supervision, as well as the unequal time of payroll. Meanwhile, the obstacles that hinder the effectiveness of the management control system on employee payroll are the Delay in Reporting Periodic Salary Increases/ Promotions, and the efforts made in the various problems faced, namely reporting employee salaries or ASN (State Civil Apparatus), and updating employment data, so that they become better and more effective.